Synthesis and characterization of nanoscale level mono/bi-ligated metal(II) complexes - Annaraj, Jamespandi (Malaysian NANO-An International Journal, 2023)
A series of nanoscale level metal complexes with bidentate (N2MCl2) and tetradentate (MN) chromophores as cisplatin analogues and intercalating agents of, [M(phen)Cl2] (1- 3), [M(bpy)Cl2] (4-6), [M(phen)2] (7-9) and [M(bpy)2] (10-12) (where respectively M = Cu(II), Ni(II) or Zn(II); phen = 1,10-phenanthroline and bpy = 2,2’-bipyridine) respectively were prepared in the present investigation. These complexes were prepared by sonochemical technique and characterized using elemental, spectral, and electrochemical techniques. Their nanorod or stick morphologies and crystalline nature were evaluated with scanning electron microscopy (SEM). Metal complexes, 1-6 are existing with two labile chlorides similar to the chemotherapeutic inorganic drug cisplatin, which may anticipate binding covalently with herring sperm DNA, While, complexes, 7-12 may undergo an intercalative mode of binding due to their structural differences relative to 1-6.